Connective Tissue Characteristics around Healing Abutments of Different Geometries: New Methodological Technique under Circularly Polarized Light. (10th October 2013) - Delgado‐Ruiz, Rafael Arcesio; Calvo‐Guirado, Jose Luis; Abboud, Marcus; Ramirez‐Fernandez, Maria Piedad; Maté‐Sánchez de Val, José Eduardo; Negri, Bruno; Gomez‐Moreno, Gerardo; Markovic, Aleksa
Abstract Purpose To describe contact, thickness, density, and orientation of connective tissue fibers around healing abutments of different geometries by means of a new method using coordinates. Materials and Methods Following the bilateral extraction of mandibular premolars (P2, P3, and P4) from six fox hound dogs and a 2‐month healing period, 36 titanium implants were inserted, onto which two groups of healing abutments of different geometry were screwed: Group A (concave abutments) and Group B (wider healing abutment). After 3 months the animals were sacrificed and samples extracted containing each implant and surrounding soft and hard tissues. Histological analysis was performed without decalcifying the samples by means of circularly polarized light under optical microscope and a system of vertical and horizontal coordinates across all the connective tissue in an area delimited by the implant/abutment, epithelium, and bone tissue. Results In no case had the connective tissue formed a connection to the healing abutment/implant in the internal zone; a space of 35 ± 10 μm separated the connective tissue fibers from the healing abutment surface. The total thickness of connective tissue in the horizontal direction was significantly greater in the medial zone in Group B than in Group A (p < .05). The orientation of the fibers varied according to the coordinate area so that internal coordinates showed a higher percentage of parallel fibers in Group A (p < .05) and a higher percentage of oblique fibers in Group B (p < .05); medial coordinates showed more oblique fibers (p < .05); and the area of external coordinates showed the highest percentage of perpendicular fibers (p < .05). The fiber density was higher in the basal and medial areas (p < .05). Conclusions Abutment geometry influences the orientation of collagen fibers; therefore, an abutment with a profile wider than the implant platform favors oblique and perpendicular orientation of collagen fibers and greater connective tissue thickness.